IMPLEMENTASI KURIKULUM MERDEKA DI MADRASAH TSANAWIYAH SUNAN KALIJAGA BAWANG KABUPATEN BATANG - Edy Mustofa; Nor Miyono; Rasiman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum at MTs Sunan Kalijaga Bawang, Batang Regency, focusing on three main aspects: planning, implementation, and evaluation. The research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and document analysis, analyzed using Miles and Huberman's interactive model. The results show that the planning of the Merdeka Curriculum involves module development meetings, In-House Training (IHT), and initial assessments. Key challenges at this stage include limited training time, insufficient teacher understanding, and minimal parental involvement in diagnostic assessments. The implementation phase covers the development of the Madrasah Operational Curriculum (KOM), academic supervision, and curriculum reviews. KOM was developed collaboratively but faced obstacles in gathering relevant data. Academic supervision provided constructive feedback, though the use of innovative teaching media needs improvement. Curriculum review remains internal, resulting in incomplete evaluations. Evaluation of the curriculum is conducted through monthly and annual meetings. Monthly meetings monitor program implementation and identify challenges, while annual meetings serve as a forum to plan new programs with stakeholder involvement. However, low parental participation in evaluations hampers collaboration efforts. This study concludes that the implementation of the Merdeka Curriculum at MTs Sunan Kalijaga has shown progress, though significant challenges remain. Key recommendations include enhanced teacher training, improved facilities, and stronger collaboration with parents to support the success of the Merdeka Curriculum.